A morphological and morphometric study of the right ventricular papillary muscles of autopsied heart of Bangladeshi people (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jul;15(2):131-4.The abstract of this article is available on the PubMed website